L’Île de Vaine Espérance : Du Bellay et Le Séjour d’Honneur d’Octovien de Saint Gelais (pour une nouvelle lecture du sonnet 31 des Regrets) - Polizzi, Gilles (Renaissance and Reformation / Renaissance et Réforme, 2009)
Through a confrontation between the collection Les Regrets of Du Bellay, and the narrative Séjour d’Honneur of Octovien de Saint Gelais (which appears to be either the object of comparison or a subtext of the collection), the author re-examines the genesis of sonnet 31 of Les Regrets, with respect to the topos of the island of Circe, allegorised by Saint Gelais as the “Île de Vaine Espérance.” In doing so, the author sheds light on the poem’s background and multiple references. The analysis in turn enlightens some of the poem’s oddities, through references to Franco-Italian politics of the years 1556–57.